2011
DOI: 10.1007/s10902-011-9273-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Well-Being From Personality in Adolescents and Older Adults

Abstract: The relationship between personality and well-being is dynamic and therefore should be examined within aging perspective. In study presented here we compared the prediction of well-being from personality in two samples-223 adolescents attending highschool (16-19 years; M = 16.94, SD = 0.51) and 134 older adults (54-90 years; M = 77.20, SD = 7.39) living in retirement home or at home. Different aspects of wellbeing were included in the study. Subjective well-being was measured with Index of WellBeing, but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 22 publications
3
40
0
1
Order By: Relevance
“…Once again, this is consistent with previous work supporting a stronger relationship between personality and well-being for PWB than SWB (Butkovic et al, 2012;Grant et al, 2009) and reinforces the distinctiveness of these dimensions.…”
Section: Well-being and The Bigsupporting
confidence: 91%
See 2 more Smart Citations
“…Once again, this is consistent with previous work supporting a stronger relationship between personality and well-being for PWB than SWB (Butkovic et al, 2012;Grant et al, 2009) and reinforces the distinctiveness of these dimensions.…”
Section: Well-being and The Bigsupporting
confidence: 91%
“…Second, PWB dimensions showed a slightly stronger relationship with the Big 5 than did SWB dimensions. Butkovic et al (2012) likewise reported that personality explained more variance in PWB than SWB. Third, consistent with Schmutte and Ryff (1997), PWB showed a more diverse relationship with personality than did SWB.…”
Section: Well-being and The Bigmentioning
confidence: 93%
See 1 more Smart Citation
“…Very few studies have compared well-being in adolescents and adults but those that have, indicate that the relationship between personality and well-being is connected to life-span development (e.g. Butkovic et al 2012). For example, data on the dynamics of neuroticism may elucidate the dynamics of well-being (Costa et al 1986).…”
Section: The Role Of Gender and Agementioning
confidence: 99%
“…Third, another point of criticism may lie in the investigation of personality within this study. In literature (Butkovic, Brkovic & Bratko, 2012;Szirmák, 2005) a five-factor model of personality is mainly described. In the present study, just three personality traits have been taken into account.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%